Tingkat Kepuasan Mahasiswa Profesi Kedokteran Gigi terhadap Aktivitas Klinik Online selama Pandemi Covid-19 Berdasarkan Kesiapan Sarana dan Prasarana - Sindystya Widiasri Arum Kumala; Masniari Novita; Hestieyonini Hadnyanawati (FORIKES, 2023)
Satisfaction with the learning process is very important for student learning outcomes. Online learning during the Covid-19 pandemic became a factor that could influence satisfaction with learning. The learning concept is different from face-to-face learning activities, namely the completeness of online learning supporting facilities and infrastructure can affect student learning satisfaction. The purpose of this study was to determine the level of satisfaction of professional students at the Faculty of Dentistry, University of Jember with online clinical activities during the Covid-19 pandemic based on the readiness of professional student facilities and infrastructure. Data was collected by filling out questionnaires and then analyzed descriptively in the form of frequency and proportion. The results of the analysis showed that the majority satisfaction level for each factor was: accessibility = 70.55% satisfied, device ownership = 88.22% satisfied, ease of receiving material = 44.55% satisfied, interactivity = 60.73% satisfied, and accuracy of the method = 64.37% satisfied. It was concluded that dental professional students were satisfied with the online learning process during the Covid-19 pandemicKeywords: online learning; dental profession students; satisfaction; the Covid-19 pandemic ABSTRAK Kepuasan terhadap proses pembelajaran sangat penting artinya bagi hasil belajar mahasiswa. Pembelajaran secara online di masa pandemi Covid-19 menjadi faktor yang dapat mempengaruhi kepuasan pelaksanakan pembelajaran. Konsep pembelajaran yang berbeda dari kegiatan pembelajaran tatap muka, yakni kelengkapan sarana dan prasarana penunjang pembelajaran online dapat mempengaruhi kepuasan pembelajaran mahasiswa. Tujuan penelitian ini adalah mengetahui tingkat kepuasan mahasiswa profesi Fakultas Kedokteran Gigi Universitas Jember terhadap aktivitas klinik online selama pandemi Covid-19 berdasarkan kesiapan sarana dan prasarana mahasiswa profesi. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis secara deskriptif berupa frekuensi dan proporsi. Hasil analisis menunjukkan bahwa tingkat kepuasan mayoritas bagi tiap-tiap faktor adalah: aksesibilitas = 70,55% puas, kepemilikan perangkat = 88,22% puas, kemudahan menerima materi = 44,55% puas, interaktivitas = 60,73% puas, dan ketepatan metode = 64,37% puas. Disimpulkan bahwa mahasiswa profesi kedokteran gigi puas terhadap proses pembalajaran online selama masa pandemi Covid-19.Kata kunci: pembelajaran online; mahasiswa profesi kedokteran gigi; kepuasan; pandemi Covid-19